A Review of Recent Progress in β‐Ga2O3 Epitaxial Growth: Effect of Substrate Orientation and Precursors in Metal–Organic Chemical Vapor Deposition. Issue 8 (9th December 2022) - Waseem, Aadil; Ren, Zhongjie; Huang, Hsien-Chih; Nguyen, Kristen; Wu, Xihang; Li, Xiuling
Abstract : Gallium oxide (Ga2 O3 ) is a highly promising ultrawide‐bandgap semiconductor for power electronics that emerged about a decade ago. Epitaxial growth Ga2 O3 at the small scale is demonstrated. In order to develop scalable manufacturing of high‐performance epitaxial structures, in‐depth understanding of the fundamental growth processes, control parameters, and mechanism is imperative. This review discusses the recent progress in epitaxial growth of β‐Ga2 O3 films and highlights challenges in obtaining high growth rate, low defects, and high carrier mobilities. Compared with the other epitaxy methods, metal–organic chemical vapor deposition (MOCVD) offers a wider growth window and precursor selection option, to minimize the tradeoff between crystal quality and growth rate. Growth rate is inversely proportional to temperature, within a certain temperature window, because of the unavoidable premature gas‐phase reactions and desorption of the highly volatile gallium suboxide (Ga2 O) at elevated temperatures. Growth defects, background impurity incorporation, and carrier mobilities can be affected by the choice of MOCVD precursors, nucleation, and adsorption/desorption/diffusion of adatoms on substrate surfaces of different orientations, including the effect of growing on cleavage and noncleavage planes. This review summarizes the current status of the epitaxial growth of β‐Ga2 O3 and analyzes the major factors that enhance mobility and reduce background doping concentration. The insights gained help advance the manufacturability of device‐grade epitaxial thin films. Abstract : Gallium oxide (Ga2 O3 ) is a highly promising ultrawide‐bandgap semiconductor for power electronics. This review discusses the recent progress in epitaxy of β‐Ga2 O3 films and highlights the challenges in obtaining high growth rate, low defects, and high carrier mobilities, including the effect of precursors and substrate orientations. The insights gained help advance the manufacturability of device quality structures.